Electrophysiological characterization of acutely isolated spiral ganglion neurons in neonatal and mature sonic hedgehog knock-in mice. (1st January 2020) - Lu, Jiawen; Liu, Huihui; Lin, Shanshan; Li, Chao; Wu, Hao
Highlights: For the convenience of SGN studies such as patch-clamp or single cell RNA-sequence studies, we generated a knock-in mouse (Shh CreEGFP/+ ; Rosa26-Tdtomato loxp/+ ) for the purpose of obtaining fluorescence SGNs. In this paper, we verified the hearing function and SGN morphology of shh knock-in mice, which were found to be normal as compared with those of wild type mice. Thus, shh knock-in mice could be used as an ideal tool to study the function and characteristics of spiral ganglion neurons. We successfully patched fluorescent SGNs under a fluorescence microscope and recorded prominent inward and outward currents, indicative of voltage-dependent sodium and potassium currents in neonatal mice. We access the membrane and firing properties of SGNs from wild type and shh mice. We provide the report of IK + from acutely isolated SGNs from adult mice; the density of IK + were significantly different from those of neonatal mice. We used cisplatin administration to study the ototoxicity and found that the effects of a low dose of cisplatin (0.5 mM correspond to therapeutic doses) causes a decrease in current and is reversible after a short administration time. Moreover, we propose the activation state of potassium channels has changed which leads to the accumulation of potassium ions and induced AP firing obstacles. However, the number and characteristic remain still after cisplatin administration. Abstract: Spiral ganglion neurons (SGNs) are primary afferent auditory neurons activated by inner hair cells in mammalian cochlea. Here, for the convenience of SGN studies such as patch-clamp or single cell RNA-sequence studies, a knock-in mouse (Shh CreEGFP/+ ; Rosa26-Tdtomato loxp/+ ) was generated for the purpose of obtaining fluorescence SGNs. Auditory brainstem response (ABR) and Tuj1 immunohistochemistry staining were performed to verify the hearing function and the morphological characteristics. The results showed that there was no significant difference between shh and wild type mice. In electrophysiological studies, we verified a series of electrophysiological characteristics including the amplitude of sodium and potassium currents and action potential characteristics of shh and wild type mice and no significant differences were found either. From the above, shh mice have the same cell function and morphology as their littermate control wild type mice and could be used as an ideal tool to study the function and characteristics of spiral ganglion neurons. Potassium channels of SGNs play an important role in resolving time accuracy. We obtained similar amplitude of IK + in neonatal and mature mice in the aging competition experiment, however, the density of IK + from mature mice were significantly different from those of neonatal mice, a phenomenon that may play a key role in the nervous system. Potassium channels have been shown to contribute to apoptosis induced by cisplatin administration in various cell lines. Here we used cisplatin administration to study the ototoxicity and found that the effects of a low dose of cisplatin (0.5 mM correspond to therapeutic doses) causes a decrease in currents and is reversible after a short administration time. Moreover, we propose the activated state of potassium channels has changed but the characteristic and number remain still after cisplatin administration. The excess potassium ions may accumulate in the cell body, which had affected the firing properties and induce cytotoxicity and apoptosis. We suggest that the electrophysiological properties of acutely isolated SGNs may support further research on the mechanics of auditory propagation and ion channel pharmacology.